KEARIFAN EKOLOGIS LOKAL SEBAGAI ALTERNATIF MODEL PEMBANGUNAN BERKELANJUTAN DI TENGAH INDUSTRIALISASI - Dion Ario; Swandi Aliverchan S; Andi Wibowo; Predy Gunawan; Aullia Vivi Yulianingrum (Jurnal Multidisipliner Kapalamada, 2025)
This study examines the role of local ecological wisdom as an alternative model for sustainable development amid the dominance of modern industrialization, which often leads to environmental degradation and social inequality. The research adopts a qualitative approach using a literature-based study design, combining conceptual analysis with a political ecology perspective to explore the relationships among industrialization, power dynamics, and natural resource governance. The findings indicate that local ecological wisdom embedded in indigenous communities—such as customary norms, conservation traditions, and community-based resource management systems—plays a significant role in maintaining ecological balance, strengthening social cohesion, and preserving cultural identity. Integrating local wisdom into development policies is therefore considered relevant for mitigating the negative impacts of industrialization and promoting more just, inclusive, and sustainable development. This study provides analytical and normative contributions to the discourse on sustainable development and environmental governance rather than generalizable empirical conclusions.